COMPARATIVE RETROTRANSPOSON ANALYSIS in WHEAT - Elif Karlık; Seray Altıntaş; Bekir Ahmet Ilgar (Journal of Advanced Research in Natural and Applied Sciences)
The presence of retrotransposons is associated with polyploidy, especially in wheat, and may cause an increase in genome size. In this study, the evolutionary information was aimed to reveal based on the comparison retrotrans-poson movements between bread and einkorn wheat Siyez. For that reason, the transposition of BARE1, Sukkula and Nikita retrotransposons in bread and einkorn wheat Siyez were analysed by using IRAP-PCR molecular mark-er method. Both monomorphic and polymorphic bands in each wheat species have been demonstrated. IRAP-PCR products of Sukkula retrotransposon was showed as 10 bands in bread wheat, but no bands could be deter-mined in einkorn wheat. Nikita retrotransposon was demonstrated as 6 bands in bread wheat, 14 bands in einkorn wheat Siyez. Polymorphism rate was calculated as 81% for Nikita between bread wheat and einkorn wheat Siyez. However, the presence of BARE1 were not observed in both species. The obtained findings suggest that Nikita retrotransposon contributes to genome obesity, especially in bread wheat. The failure of Sukkula retrotransposon detection in einkorn wheat Siyez indicates that Sukkula may be inserted in the genome of bread wheat by horizon-tal gene transfer during wheat domestication events. These results may provide to uncover the organization of wheat genome during domestication.